ANALISIS PEMASARAN KUBIS (Brassica oleracea L. var. cagitata L) DI SUB TERMINAL AGRIBISNIS (STA) JETIS KABUPATEN SEMARANG - Istanto Istanto; Wiludjeng Roessali; Agus Setiadi (Universitas Wahid Hasyim, 2016)
The purpose of this study was to determine the marketing system and the number of marketing channels cabbage in Jetis STA Semarang District. This research method is descriptive qualitative by using primary and secondary data. Collecting data in this study by observation, interviews and questionnaires. The research location is in Jetis STA Semarang District. The number of respondents as 58 people consisting of five wholesalers respondents, and 3 employees STA Jetis respondents with method purposive. While 5 farmer respondents, 10 merchant middleman respondents, 15 merchants collector respondents, 15 retailers respondents, and 5 consumers respondents with a method Accidental sampling. The results showed that the cabbage marketing system that is in STA Jetis is conventional marketing systems, is marketing system that gives full discretion to each marketing agencies and agricultural producers to run each their business. The cabbage marketing channels in STA Jetis consists of seven patterns of marketing channels as follows: (1) Farmer - Traders Village - Collector - Wholesalers - Retailers - Consumer, (2) Farmers - Collector - Wholesalers - Retailers - Consumer , (3) Farmer - Traders Village - Wholesalers - Retailers - Consumer, (4) Farmer - Wholesalers - Collector - Retailers - Consumer (5) Farmer - Collector - Consumer (6) Farmer - Traders Village - Collector - Retailers - Consumer, and (7) Farmers - Collector - Consumer. Keywords: Cabbage, channel marketing, marketing system.